Dispensasi Nikah Dalam Perspektif Hukum Islam, Undang-Undang Nomor 1 Tahun 1974 dan Kompilasi Hukum Islam - Kamarusdiana Kamarusdiana; Ita Sofia (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
AbstractMarriage dispensation is a legal solution because most of the perpetrators of marriage dispensation are those who do not yet have formal legality to get married, so they then take the legal initiative so that marriages can be recognized. This study aims to determine the perspective of Islamic law, Marriage Law and Compilation of Islamic Law regarding marriage dispensation. The method used is qualitative with primary data sources from the Marriage Law, the Book of Fiqh and the Compilation of Islamic Law while secondary data are books, journals, magazines related to marriage dispensation. The results of this study found that Islamic law does not specifically regulate marriage dispensation because the majority of scholars only mention balig as a condition for marrying a person and do not specify a minimum age of marriage, whereas Law Number 1 of 1974 concerning Marriage and Compilation of Islamic Law strictly regulates underage marriage , i.e. must go through a court hearing mechanism to obtain a marriage dispensation permit.Keywords: Marriage Dispensation, Compilation of Islamic Law AbstrakDispensasi Nikah sebagai solusi hukum karena para pelaku dispensasi nikah kebanyakan mereka yang belum memiliki legalitas formal untuk menikah, sehingga kemudian mengambil ikhtiar hukum agar pernikahan yang dilakukan dapat diakui. Penelitian ini bertujuan mengetahui perspektif hukum Islam, Undang-undang Perkawinan dan Kompilasi Hukum Islam tentang dispensasi nikah. Metode yang digunakan adalah kualitatif dengan sumber data primer dari Undang-Undang Perkawinan, Kitab Fiqh dan Kompilasi Hukum Islam sedangkan data sekunder adalah buku-buku, jurnal, majalah yang terkait dengan dispensasi nikah. Hasil penelitian ini menemukan bahwa Hukum Islam tidak mengatur khusus dispensasi nikah karena mayoritas ulama hanya menyebutkan balig sebagai syarat menikah seseorang dan tidak menentukan minimal usia perkawinan, sedangkan Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan dan Kompilasi Hukum Islam mengatur ketat tentang perkawinan di bawah umur, yaitu harus melalui mekanisme sidang pengadilan untuk mendapatkan izin dispensasi perkawinanKata Kunci: Dispensasi Nikah, Kompilasi Hukum Islam